Fuzzy Nonlinier Mix-Integer Goal Programming with Genetic Algorithms - Samsuryadi Samsuryadi (Jurnal Penelitian Sains, 2003)
System’s reability optimization problems are modeled using fuzzy nonlinier mix-integer goal programming problems, involving imprecise nonlinier mix-integer information. Furthermore, fuzzy nonlinier mix-integer goal programming is transformed into nonlinier mix-integer programming problem and the problem i solved using genetic algorithms by means of Matlab 5.3 software. The results or genetic algorithms with operator arithmetic crossover are the large of initial population number does not give the better fitness and the more generation numbers will result more high fitness.